Effectiveness of Differentiated Strategy Implementation on Minimum Competency Assessment Ability of 5 Grade Students in Public Elementary Schools - Novia Setyoningtyas; Sri Utaminingsih; Ahmad Hariyadi (Pascasarjana Universitas KH. Abdul Chalim, 2026)
The issue of the Minimum Competency Test (AKM) in Indonesia is a crucial educational problem because it affects the quality of learning, students' academic development, and the effectiveness of the education system. This study aims to examine the effect of implementing differentiation strategies on improving students’ literacy and numeracy skills in elementary schools, particularly in the context of AKM. Using a quantitative experimental design, this study involved two groups of students: an experimental group that implemented differentiation strategies and a control group that used traditional teaching methods. Data were collected through pre-tests and post-tests to measure changes in literacy and numeracy skills. The results showed that the experimental group experienced a significant increase in AKM scores compared to the control group. The average post-test score in the experimental group increased substantially, while the control group showed only a small increase. These findings confirm that differentiation strategies are effective in improving students’ literacy and numeracy skills. This study also shows that teaching tailored to individual student needs can yield better results in AKM. The results of this study are expected to provide educators and policymakers with valuable insights for designing more effective and inclusive teaching methods to improve the quality of education in Indonesia. Thus, differentiation strategies can be a solution in overcoming the challenges of low literacy and numeracy among Indonesian students, as well as improving overall competency test results.